Transformation Of Islamic Religious Education Teacher's Exemplary Role In Shaping Students' Religious Attitudes (A Case Study at Madrasah Tsanawiyah Al-Hidayah Wajak 2025) - Nur Qomari (CV PUTRA PUBLISHER, 2025)
This study explores the role of the exemplary behavior of Islamic Religious Education (PAI) teachers at MTs Al-Hidayah Wajak in shaping student religiosity. The findings indicate that teacher exemplary behavior functions as a tangible model for applying Islamic values in daily life, creating a religious environment that supports the internalization of religious values. Although challenges such as social media influence and time constraints exist, institutional support and digital technology can enhance the effectiveness of role modeling. This study concludes that the exemplary behavior of PAI teachers is a crucial strategy in sustainable character education, shaping students who are both academically excellent and morally mature.